Near-Infrared Fluorescence Imaging and Photodynamic Therapy for Liver Tumors - Kaibori, Masaki; Kosaka, Hisashi; Matsui, Kosuke; Ishizaki, Morihiko; Matsushima, Hideyuki; Tsuda, Takumi; Hishikawa, Hidehiko; Okumura, Tadayoshi; Sekimoto, Mitsugu (Frontiers in Oncology, 2021)
In recent years, the use of fluorescence-guided surgery to treat benign and malignant visceral, hepatobiliary and pancreatic neoplasms has significantly increased. Optical imaging using near-infrared (NIR) fluorescence can be used to assess anatomy and function during both open and minimally invasive surgeries in real time. This article reviews the published literature related to clinical applications of NIR fluorescence imaging during liver surgery. We have developed a new nanoparticle (Indocyanine green Lactosome) that is biocompatible and can be used for imaging cancer tissues and as a drug delivery system. To date, stable particles have been formed in blood (half-life in blood: 10–20 hours); particles labeled with a NIR fluorescent agent have been applied to cancer tissues by the enhanced permeability and retention effect, in mice. We review recent developments in photodynamic therapy, which may contribute to development of innovative treatments for liver tumors.